Politeness in Expressive Speech Acts: A Cyber Pragmatics Approach - Fatmawati, Famawati; Ningsih, Rika (Universitas Pendidikan Mandalika, 2024)
This research is motivated by the tendency of netizens to convey psychological attitudes on social media. The delivery of these psychological attitudes sometimes needs attention to language politeness. This research is necessary because it answers the challenge of understanding how politeness of language changes in the context of social media supported by digital technology, which is rarely discussed in conventional pragmatic studies. The problem in this study is how politeness of expressive speech acts from a cyber pragmatics perspective. This study explores and elaborates on the realization of politeness maxims politeness principles based on the perspective of cyber pragmatics. The approach used in this study is qualitative, and the content analysis method was applied. This study's data source is netizens' language activity on the comments page of the Instagram account @detikcom on June 9, 2023, totaling 2509 comments. The data in this study amounted to 511 data, which are expressive speech. The data collection techniques used are documentation techniques and reading techniques. The data analysis technique is carried out in three stages: identification, classification, and interpretation of research results. Regarding the principle of politeness, netizens' comments are considered impolite based on the maxim of tact, the maxim of approbation, and the maxim of agreement, which significantly impact online communication behavior. The reason is that netizens do not maximize their benefits, approbation, and conformity with other parties but instead express their psychological attitudes by throwing out insults, ridicule, and rejections that can cause harm to other parties. Meanwhile, netizens are considered polite for the maxim of modesty and sympathy. Most sympathy is directed at the Indonesian people who must bear the country's debt.